1986
DOI: 10.1017/s002214300001220x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation distribution in terre adélie, antarctica: effect of meteorological parameters

Abstract: ABSTRACT. Along the 1040 km extending from Cape Prud'homme (lat.66°4I'S., long.139°55'E.), near Dumont d'Urville station, to Dome C (lat. 74 °39 , S., long. 124 ° 10' E.), the variations in annual accumulation can be analysed by a division of the entire data set into three sub-sets depending on the types of measurements and the character of the spatial distribution. Along the first 33 km, from the coast to stake E40, annual measurements show considerable inter-annual variability, 52% of which can be explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 10 publications
(9 reference statements)
2
33
0
Order By: Relevance
“…Wind erosion, wind redistribution, sublimation, and other processes during or after the precipitation event lead to a deposition at the surface which is spatially less homogeneous than the original precipitation. Variations in accumulation over tens of kilometers have been observed since the 1960s [Black and Budd, 1964;Pettré et al, 1986]. These accumulation variations and surface processes result in surface features including sastrugi, longitudinal dunes [Goodwin, 1990], dunes on the 100-m scale Karlöf et al, 2005b], and, most impressively, megadunes on a kilometer scale [Fahnestock et al, 2000;Frezzotti et al, 2002a].…”
Section: Principal Processesmentioning
confidence: 99%
“…Wind erosion, wind redistribution, sublimation, and other processes during or after the precipitation event lead to a deposition at the surface which is spatially less homogeneous than the original precipitation. Variations in accumulation over tens of kilometers have been observed since the 1960s [Black and Budd, 1964;Pettré et al, 1986]. These accumulation variations and surface processes result in surface features including sastrugi, longitudinal dunes [Goodwin, 1990], dunes on the 100-m scale Karlöf et al, 2005b], and, most impressively, megadunes on a kilometer scale [Fahnestock et al, 2000;Frezzotti et al, 2002a].…”
Section: Principal Processesmentioning
confidence: 99%
“…This difficulty does not prevent from obtaining reliable observed SMB data in studied areas, as attested by other reliable SMB measurement methods in most of the previous cited works. However, several authors showed very large standard deviations (up to 150%) in the accumulation pattern derived from annual SMB stake farms (or single stake) measurements [Petit et al, 1982;Pettre et al, 1986;Mosley-Thompson et al, 1999;Goodwin et al, 2003;Frezzotti et al, 2005]. As pointed out by Fisher et al [1985], the observed variability limits the degree to which a single annual snow accumulation value may be temporally representative of the local SMB on longer period.…”
Section: Stakes Measurements (Stake Farms and Single Stakes): Rates Amentioning
confidence: 99%
“…Wind velocities at South Pole are quite high, particularly during winter months, and we hypothesize that the very large stake-to-stake variability in monthly accumulation is primarily caused by these high winds since snow transport is highly dependent on wind speed [Pomeroy and Jones, 1996;Pettre et al, 1986]. The standard deviation in gross monthly accumulation is plotted in Figure 7, along with two indicators of windiness during each accumulation month.…”
Section: Extension To Other Polar Ice Coring Sitesmentioning
confidence: 99%